Collaboration Between Jimbaran Indigenous Village Government and Civil Society in Addressing Impacts of Covid-19 Crisis - Antari, Ni Putu Bayu Widhi; Lestari, Ni Luh Yuni (UI Scholars Hub, 2022)
This paper aims to explain the collaboration between the Jimbaran indigenous village government and civil society in addressing the impacts of the COVID-19 Crisis. Additionally, it also explains why collaboration between those actors occurred. Utilizing an interpretive approach, this phenomenological study uncovers the collaboration between the indigenous village government and civil society in Jimbaran Regency, Bali. The data is collected through desk study, observation, and semi-structured interviews. Based on the data analysis, collaboration is initiated by civil society through their creative ideas. It was then discussed and supported by the legitimate actor from the regency, the ward, and the indigenous village government. This collaboration, which occurred in economic and health activities, can be carried out thanks to the existence of rules, actors' understanding of citizens' needs, religious values and actors' principles, complementary roles between the indigenous village government and civil society, strong actors' commitment, understanding of the benefits of collaboration, stakeholders' appreciation, and the roles of the head of the citizen empowerment unit (CEU) as an enabler of this collaboration. According to these findings, it is understood that the involvement of organizations with informal and formal legitimation is required in carrying out activities to address complex crises such as COVID-19. The actors also should involve in both the economic and health aspects of the crises because these aspects significantly impact livelihood. Local values play significant roles in strengthening collaboration.